Rapport de l’atelier formation des agropasteurs de Gonaky en production et gestion du fourrage et en bonnes pratiques d’hygiène dans la traite et la gestion du lait - Mbow, Khalifa; Worou, Nadine; Ka, Binetou; Huyer, Sophia; Diallo, Abdoulaye Moussa; Diedhiou, Lamine (International Livestock Research Institute, 2024)
This report documents the training workshop organised in Gonaky as part of the AICCRA project, covering fodder production and management as well as good hygiene practices related to milking and milk management. The aim of this initiative was to build the capacity of agropastoralists, particularly women, to improve their resilience in the face of the impacts of climate change on livestock and milk production. The workshop, led by experts from ISRA, ILRI and AICCRA, covered key topics such as sustainable management of fodder resources, fodder conservation techniques, and hygiene standards to guarantee milk quality. The active participation of agropastoralists enabled them to discuss the challenges they faced and identify solutions adapted to their context. Feedback from participants underlines the importance of these training courses for adopting climate-smart farming practices and improving the socio-economic conditions of rural communities. This report highlights the positive impact of such initiatives on food security, the sustainability of pastoral production systems and the empowerment of rural women. It also proposes recommendations for increased adoption of the innovations presented at the workshop.